Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO